SILON APPLICATION AS AN IMPLEMENTATION OF E-GOVERNMENT IN THE DPRD NOMINATION STAGE IN THE 2024 ELECTION AT KPU BALI PROVINCE - Sanjaya Putri, Putu Adinda Prameswari; Wirya Darma, I Made (LPPM Univ. Ibn Khaldun Bogor, 2023)
Today’s people live in a time when everything is required to process quickly and easily, with the help of sophisticated technology and Internet access. The concept of the e-government is a governmental tool of information technology to provide information and services that are effective, efficient, and transparent to the public in the process of emitting good government. KPU Provinsi Bali since the 2019 simultaneous elections, has been using an application that is intended to help facilitate the stages of running for elections known as SILON a candidacy information system. As a result, all data relating to applications for requirements by the political party for electoral participants as well as the individual council of regional representatives throughout Indonesia can be properly managed and well documented, and a complex and laborious succession of stages can be completed more effectively and efficiently, as well as paperless.